Prosodic Structure in Child French: Evidence for the Foot - Heather Goad (Universitat Autònoma de Barcelona, 2006)
There is disagreement in the literature on whether French has stress and on whether it has a foot projection. The disagreement stems from the observation that French is unusual in that the phrase rather than the word is the domain of stress assignment, there is optional initial stress in addition to obligatory final stress, and there are rampant violations of word minimality. In view of these observations, this paper examines the outputs of a child learner of Québec French in an attempt to determine the conclusions she has arrived at concerning the status of the foot in the language being acquired. It is demonstrated that, in spite of the challenge that the facts of the target language present, from the onset of production, the child’s outputs are compatible with standard views on prosodic structure. Word minimality effects, the distribution of final lengthening, the emergence of word-final consonants, and the organisation of functional material into prosodic structure are all examined. The paper also provides a preliminary analysis of stress in target French which is, to the greatest extent possible, consistent with standard views on prosodic structure.